Fine adjustment method for structural color of block copolymer-based structural color material

By performing a multi-step polymerization reaction in a series microreactor, the reaction parameters are finely adjusted, and block copolymer-based structural color materials are prepared, which solves the problem of complex and difficult to scale the preparation of structural color materials in traditional methods, and achieves fine adjustment and large-scale production of structural color materials.

CN119751890AActive Publication Date: 2025-04-04TIANJIN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411934935.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The traditional colloidal particle stencil method is complex and difficult to apply on a large scale. The structural period size generated by self-assembly of conventional block copolymers is less than 100 nm, and the photon band gap cannot be generated in the visible light area, making it difficult to finely adjust and reproduce the structural color.

Method used

The block copolymer was prepared by a series microreactor. Through multi-step polymerization reaction and fine regulation of reaction parameters, block copolymer-based structural color materials with bright structural color and high molecular weight were prepared.

Benefits of technology

The fine adjustment and large-scale production of structural color materials are realized, the preparation cost is reduced, and the molecular weight distribution of the material and the consistency and reproducibility of structural color are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751890A_ABST
    Figure CN119751890A_ABST
Patent Text Reader

Abstract

The invention discloses a fine adjustment method for the structural color of a block copolymer-based structural color material, and belongs to the technical field of high polymer materials. The fine adjustment method for the structural color of the block copolymer-based structural color material comprises the following steps: mixing a monomer 1 and a catalyst solution, then carrying out a first polymerization reaction, mixing a product and a monomer 2, then carrying out a second polymerization reaction to obtain a block copolymer, and carrying out self-assembly on the block copolymer to obtain the block copolymer-based structural color material. According to the method, continuous and efficient preparation of the structural color material can be achieved, large-scale production of the structural color material is further achieved, and the preparation cost of the structural color material can be remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a method for finely adjusting the structural color of a block copolymer-based structural color material. Background Art

[0002] Structural color originates from the Bragg reflection of periodic nanostructures. This type of material has the advantages of being safe, environmentally friendly, beautiful, resistant to light drift, and responsive to stimuli. It is expected to replace traditional toxic pigments for use in cosmetics, environmentally friendly coatings, safe painting pigments, anti-counterfeiting inks and other fields. Common photonic crystal structures include one-dimensional layered structures, two-dimensional columnar dense-packed structures and three-dimensional spherical stacking structures. Among them, the ordered porous structure of inverse opal has a higher refractive index difference and can produce more beautiful structural colors. However, the traditional colloidal particle template method has a complicated preparation process and is difficult to apply on a large scale.

[0003] Block copolymer self-assembly is an effective method for preparing ordered structured polymer materials. In 1999, Thomas's research group first reported structural color materials based on linear block copolymers, and obtained a rich phase structure. However, the periodic size of conventional phase separation structures is generally <100nm, which cannot produce photonic band gaps in the visible light region. Therefore, in order to obtain structural colors, it is necessary to synthesize molecular weights higher than 1×10 6 The block copolymers of ultra-high molecular weight polymer chains are severely entangled, the self-assembly kinetics are slow, and there are many structural defects, which make it difficult to apply them in practice.

[0004] Bottle brush block copolymers (BBCPs) are ideal materials for making photonic crystal pigments. Their polymer side chains are tightly grafted onto linear backbones, which can reduce entanglement and quickly self-assemble into photonic crystal structures with large period sizes exceeding 100 nm. However, the preparation of bottle brush block copolymer-based structural color materials is usually carried out in small batches in the laboratory, and there are still many challenges in large-scale production, including poor control of polymer molecular weight and molecular weight distribution, which makes it difficult to fine-tune the structural color and poor reproducibility of different batches. Summary of the invention

[0005] The purpose of the present invention is to provide a method for finely adjusting the structural color of a block copolymer-based structural color material to solve the problems existing in the above-mentioned prior art.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention: a method for preparing a block copolymer-based structural color material, comprising the following steps:

[0008] The monomer 1 and the catalyst solution are mixed to carry out a first polymerization reaction, the product is mixed with the monomer 2 to carry out a second polymerization reaction to obtain a block copolymer, and the block copolymer is self-assembled to obtain the block copolymer-based structural color material.

[0009] Furthermore, the preparation process of the block copolymer is carried out in a series of microreactors, which include the following devices connected in series in sequence: a first T-shaped mixer for mixing a catalyst and a solvent to prepare a catalyst solution, a second T-shaped mixer for mixing the catalyst solution and a monomer 1, a first microreactor for performing a first polymerization reaction, a third T-shaped mixer for mixing a product and a monomer 2, a second microreactor for performing a second polymerization reaction, a fourth T-shaped mixer for mixing the block copolymer and a solvent, a diluter for diluting the block copolymer, and an adsorption column for removing the catalyst.

[0010] Further, the monomer 1 and the monomer 2 are different cycloolefin polymerization monomers;

[0011] The molecular weight of the cycloolefin polymerization monomer is 500 to 10000Da;

[0012] The topological structure of the block copolymer is bottle brush type;

[0013] The temperature of the first polymerization reaction and the second polymerization reaction is 15 to 100° C.;

[0014] The inner diameter of the pores of the serially connected microreactors is 0.5 to 5 mm.

[0015] Furthermore, the microreactor is a circular tube type (made of stainless steel) or a special channel type reactor (enhanced straight tube type, Z-shaped, S-shaped, etc.).

[0016] Furthermore, the monomer 1 and the monomer 2 are independently selected from any one of polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol, polypropylene oxide, polystyrene, polydimethylsiloxane, polycaprolactone, polylactide, polytert-butyl acrylate and polymethyl methacrylate having a norbornene group.

[0017] Furthermore, the solvent includes any one of toluene, dichloromethane, chloroform, ethyl acetate, butyl acetate, anisole and phenethyl ether.

[0018] Furthermore, the self-assembly is emulsion assembly or bulk assembly.

[0019] Furthermore, the emulsion assembly comprises:

[0020] The block copolymer solution and the PVA aqueous solution are mixed and emulsified, and the block copolymer-based structural color material is obtained after the solvent evaporates.

[0021] Furthermore, the body assembly comprises:

[0022] The block copolymer solution is coated on the surface of the substrate, and the block copolymer-based structural color material is obtained after the solvent evaporates.

[0023] The second technical solution of the present invention: a block copolymer-based structural color material prepared by the above-mentioned preparation method.

[0024] The third technical solution of the present invention: an application of the above-mentioned block copolymer-based structural color material in the preparation of pigments.

[0025] Technical solution 4 of the present invention: A method for finely adjusting the structural color of a block copolymer-based structural color material, comprising the following steps:

[0026] The monomer 1 and the catalyst solution are mixed to carry out a first polymerization reaction, the product and the monomer 2 are mixed to carry out a second polymerization reaction to obtain a block copolymer, and the block copolymer is self-assembled to obtain a block copolymer-based structural color material.

[0027] Furthermore, the reflection wavelength of the block copolymer-based structural color material is 400-700 nm.

[0028] Furthermore, the preparation process of the block copolymer is carried out in a series of microreactors, which include the following devices connected in series in sequence: a first T-shaped mixer for mixing a catalyst and a solvent to prepare a catalyst solution, a second T-shaped mixer for mixing the catalyst solution and a monomer 1, a first microreactor for performing a first polymerization reaction, a third T-shaped mixer for mixing a product and a monomer 2, a second microreactor for performing a second polymerization reaction, a fourth T-shaped mixer for mixing the block copolymer and a solvent, a diluter for diluting the block copolymer, and an adsorption column for removing the catalyst.

[0029] Further, the monomer 1 and the monomer 2 are different cycloolefin polymerization monomers;

[0030] The molecular weight of the cycloolefin polymerization monomer is 500 to 10000Da;

[0031] The topological structure of the block copolymer is bottle brush type;

[0032] The temperature of the first polymerization reaction and the second polymerization reaction is 15 to 100° C.;

[0033] The inner diameter of the pores of the serially connected microreactors is 0.5 to 5 mm.

[0034] Furthermore, the microreactor is a circular tube type (made of stainless steel) or a special channel type reactor (enhanced straight tube type, Z-shaped, S-shaped, etc.).

[0035] Furthermore, the monomer 1 and the monomer 2 are independently selected from any one of polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol, polypropylene oxide, polystyrene, polydimethylsiloxane, polycaprolactone, polylactide, polytert-butyl acrylate and polymethyl methacrylate having a norbornene group.

[0036] Furthermore, the solvent includes any one of toluene, dichloromethane, chloroform, ethyl acetate, butyl acetate, anisole and phenethyl ether.

[0037] Furthermore, the self-assembly is emulsion assembly or bulk assembly.

[0038] Furthermore, the emulsion assembly comprises:

[0039] The block copolymer solution and the PVA aqueous solution are mixed and emulsified, and the block copolymer-based structural color material is obtained after the solvent evaporates.

[0040] Furthermore, the body assembly comprises:

[0041] The block copolymer solution is coated on the surface of the substrate, and the block copolymer-based structural color material is obtained after the solvent evaporates.

[0042] The present invention can precisely control the key reaction parameters in the preparation process, can prepare block copolymer-based structural color materials with bright structural colors in large quantities, and can achieve fine control of structural colors. The method of the present invention overcomes the technical bottlenecks of the inability to finely adjust the color of structural color materials in traditional intermittent preparation methods and the limitation of the synthesis scale to the gram level, and provides a feasible solution for the industrial production of bottle brush block copolymer-based structural color materials.

[0043] The present invention discloses the following technical effects:

[0044] (1) The method of the present invention can realize the continuous and efficient preparation of structural color materials, thereby realizing the large-scale production of structural color materials, and the method of the present invention can significantly reduce the preparation cost of structural color materials.

[0045] (2) The preparation method of the present invention can accurately control the molecular weight of the block copolymer-based structural color material, thereby achieving fine adjustment of the structural color, and can make the structural color material have strong and bright colors, excellent brightness and rich color saturation.

[0046] (3) The preparation method of the present invention is simple and safe to operate, and is compatible with automated production, which makes it possible to construct an efficient and low-cost color library of structural color materials. At the same time, it promotes the transformation from laboratory research to commercial products and provides a new way for the development of environmentally and health-friendly pigments.

[0047] Moreover, the synthesis strategy of the present invention has broad application prospects and can be extended to a variety of block copolymer-based assembly materials, covering multiple fields such as ultra-soft elastomers, organic optoelectronics, lithography, energy storage and biomedical equipment, etc. It provides a blueprint for industrial production, greatly reduces production costs, and promotes the development of block copolymer-based assembly materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0049] Figure 1 Schematic diagram of the continuous preparation process of block copolymer-based structural color materials;

[0050] Figure 2 The actual pictures of the polymer porous microspheres with different structural colors prepared in Example 1;

[0051] Figure 3 This is a macroscopic photograph of the structural color film prepared in Example 7;

[0052] Figure 4 Schematic diagram of the special channel reactor. DETAILED DESCRIPTION

[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0054] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0055] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0056] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0057] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0058] In a first aspect, the present invention provides a method for preparing a block copolymer-based structural color material, comprising the following steps:

[0059] Connecting the outlets of the continuous infusion pump of the solvent and catalyst solution to the two inlets of the first T-shaped mixer respectively;

[0060] Connecting the outlet of the first T-mixer to an inlet of the second T-mixer;

[0061] Connecting the outlet of the continuous infusion pump of the solution of cycloolefin polymerization monomer 1 to the other inlet of the second T-shaped mixer;

[0062] Connecting the outlet of the second T-shaped mixer to the inlet of one side of the first microreactor;

[0063] Connecting the outlet on the other side of the first microreactor to an inlet of a third T-shaped mixer;

[0064] Connecting the outlet of the continuous infusion pump of the solution of the cycloolefin polymerization monomer 2 to another inlet of the third T-shaped mixer;

[0065] Connect the outlet of the third T-shaped mixer to the inlet on one side of the second microreactor;

[0066] Connecting the outlet on the other side of the second microreactor to an inlet of a fourth T-shaped mixer;

[0067] connecting the solvent to another inlet of the fourth T-shaped mixer, and connecting the outlet of the fourth T-shaped mixer to the inlet of the diluter;

[0068] connecting the outlet of the diluter to the inlet of an adsorption column filled with a metal scavenger, and collecting the purified block copolymer solution at the outlet of the adsorption column filled with the metal scavenger;

[0069] The specific operations are as follows:

[0070] (1) The solvent and catalyst solution are uniformly mixed through a first T-shaped mixer, and then uniformly mixed with the cycloolefin polymerization monomer 1 solution through a second T-shaped mixer, and then introduced into a first microreactor for polymerization reaction (ring-opening metathesis polymerization, the polymerization reaction time is 25 to 120 seconds). After the reaction is completed, the solution flows out from the outlet on the other side of the first microreactor to obtain a first effluent.

[0071] (2) The first effluent and the solution of cycloolefin polymerization monomer 2 are mixed evenly through a third T-shaped mixer, and introduced into a second microreactor for polymerization reaction (ring-opening metathesis polymerization, the polymerization reaction time is 35 to 120 seconds). After the reaction is completed, the effluent flows out from the outlet on the other side of the second microreactor to obtain a block copolymer solution.

[0072] (3) The block copolymer solution and the solvent are mixed through a fourth T-shaped mixer, and passed into a diluter (a stainless steel round tube with an inner diameter of 2.1 to 4 mm) for dilution (online dilution) and cooling to obtain a cooled block copolymer dilution solution.

[0073] (4) Passing the cooled dilute block copolymer solution into an adsorption column filled with a metal scavenger for purification to obtain a purified block copolymer solution.

[0074] (5) Using purified block copolymer solutions for self-assembly, block copolymer-based structural color materials can be prepared in large quantities and with high precision.

[0075] The solvent, the catalyst solution, the cycloolefin polymerization monomer 1 solution, and the cycloolefin polymerization monomer 2 solution are respectively placed in a liquid storage tank provided with a continuous infusion pump; the first microreactor and the second microreactor are respectively placed in an oil bath for temperature control;

[0076] In a specific embodiment of the present invention, the catalyst in the catalyst solution is a third generation Grubbs catalyst.

[0077] In a specific embodiment of the present invention, the maximum reflection wavelength of the block copolymer-based structural color material is 400-700nm (the method of the present invention can achieve fine adjustment of the structural color, such as preparing structural color materials with maximum reflection wavelengths of 500nm, 505nm, 510nm, etc. and with extremely small reflection wavelength changes).

[0078] In a specific embodiment of the present invention, the topology of the block copolymer is bottle brush type;

[0079] The polymerization temperature is 15 to 100°C;

[0080] The inner diameters of the pipes of the first microreactor and the second microreactor are both 0.5-5 mm; the first microreactor and the second microreactor are both round tube or special channel reactors (enhanced straight tube type, Z-shaped, S-shaped, etc.); the schematic diagram of the special channel reactor is shown in Figure 4 .

[0081] In a specific embodiment of the present invention, the molecular weight of the cycloolefin polymerization monomer is 500 to 10000 Da;

[0082] The cycloolefin polymerization monomer 1 and the cycloolefin polymerization monomer 2 are independently selected from any one of polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol, polypropylene oxide, polystyrene, polydimethylsiloxane, polycaprolactone, polylactide, polytert-butyl acrylate and polymethyl methacrylate having a norbornene group, and the cycloolefin polymerization monomer 1 and the cycloolefin polymerization monomer 2 are different substances;

[0083] The solvent used in preparing the solution of cycloolefin polymerization monomer 1, the solution of cycloolefin polymerization monomer 2 and the solution of the catalyst includes any one of toluene, dichloromethane, chloroform, ethyl acetate, butyl acetate, anisole and phenethyl ether.

[0084] In a specific embodiment of the present invention, the self-assembly is emulsion assembly or bulk assembly.

[0085] In a specific embodiment of the present invention, the emulsion assembly comprises:

[0086] The purified block copolymer solution and the PVA aqueous solution are mixed and emulsified, and the block copolymer-based structural color material (structural color microspheres) is obtained after the solvent evaporates.

[0087] In a specific embodiment of the present invention, the body assembly includes:

[0088] The purified block copolymer solution is coated on the surface of the substrate, and the block copolymer-based structural color material (structural color film) is obtained after the solvent evaporates.

[0089] Furthermore, the coating method is selected from any one of spraying, scraping and brushing.

[0090] In a specific embodiment of the present invention, the concentration of the solution of cycloolefin polymerization monomer 1 is 40-86 mmol / L, and the flow rate is 0.75-12 mL / min; the concentration of the solution of cycloolefin polymerization monomer 2 is 40-300 mmol / L, and the flow rate is 0.58-28.8 mL / min; the concentration of the catalyst solution is 0.1-4.0 mmol / L, and the flow rate is 0.35-8.10 mL / min; in the first T-shaped mixer, the flow rate of the pure solvent mixed with the catalyst is 0.31-9.43 mL / min.

[0091] The schematic diagram of the continuous preparation process of block copolymer-based structural color materials is shown in Figure 1 .

[0092] In a second aspect, the present invention provides a block copolymer-based structural color material prepared by the above preparation method.

[0093] The third aspect of the present invention provides a use of the above block copolymer-based structural color material in the preparation of pigments.

[0094] In a fourth aspect, the present invention provides a method for finely adjusting the structural color of a block copolymer-based structural color material, and a method for preparing the block copolymer-based structural color material.

[0095] Example 1

[0096] A method for finely adjusting the structural color of a block copolymer-based structural color material:

[0097] (1) Setting up the reaction system: connecting the outlets of the continuous infusion pumps of the solvent and catalyst solutions to the two inlets of the first T-shaped mixer respectively;

[0098] Connecting the outlet of the first T-mixer to an inlet of the second T-mixer;

[0099] Connecting the outlet of the continuous infusion pump of the solution of cycloolefin polymerization monomer 1 to the other inlet of the second T-shaped mixer;

[0100] Connecting the outlet of the second T-shaped mixer to the inlet of one side of the first microreactor;

[0101] Connecting the outlet on the other side of the first microreactor to an inlet of a third T-shaped mixer;

[0102] Connecting the outlet of the continuous infusion pump of the solution of the cycloolefin polymerization monomer 2 to another inlet of the third T-shaped mixer;

[0103] Connect the outlet of the third T-shaped mixer to the inlet on one side of the second microreactor;

[0104] Connecting the outlet on the other side of the second microreactor to an inlet of a fourth T-shaped mixer;

[0105] connecting the solvent to another inlet of the fourth T-shaped mixer, and connecting the outlet of the fourth T-shaped mixer to the inlet of the diluter;

[0106] The outlet of the diluter is connected to the inlet of an adsorption column filled with a metal scavenger, and the purified block copolymer solution is collected at the outlet of the adsorption column filled with a metal scavenger.

[0107] (2) Solution preparation: NB-PCL (norbornene-terminated polycaprolactone) macromonomer (molecular weight of 3000 Da, molecular weight distribution index of 1.10), NB-PEG (norbornene-terminated polyethylene glycol) macromonomer (molecular weight of 2000 Da, molecular weight distribution index of 1.09), and Grubbs third-generation catalyst (relative molecular weight of 884.53 Da) were prepared into 86 mmol / L, 86 mmol / L, and 2.5 mmol / L NB-PCL ultra-dry toluene solution, NB-PEG ultra-dry toluene solution, and Grubbs third-generation catalyst ultra-dry toluene solution, respectively;

[0108] The NB-PCL ultra-dry toluene solution, the NB-PEG ultra-dry toluene solution, the Grubbs third-generation catalyst ultra-dry toluene solution (catalyst solution) and the pure toluene solvent were placed in a reservoir with a continuous infusion pump, respectively.

[0109] (3) Polymer synthesis: The catalyst solution (flow rate set to 0.64 mL / min) and pure toluene solvent (flow rate set to 0.41 mL / min) were mixed evenly in the first T-shaped mixer, and then mixed evenly with NB-PCL ultra-dry toluene solution (solution of cycloolefin polymerization monomer 1, flow rate set to 0.75 mL / min) through the second T-shaped mixer, and then introduced into the first microreactor (stainless steel round tube reactor, the inner diameter of the tube is 500 μm, the reactor is placed in a 70°C constant temperature oil bath for heating) for polymerization reaction (ring-opening metathesis polymerization), the residence time is 25 s (the length of the stainless steel round tube is adjusted so that the residence time of the reactants in the first microreactor is 25 s), and after the reaction is completed, the first effluent is obtained from the outlet on the other side of the first microreactor;

[0110] The first effluent and the NB-PEG ultra-dry toluene solution (a solution of cycloolefin polymerization monomer 2, with a flow rate set to 1.05 mL / min) were mixed evenly by a third T-shaped mixer, and passed into a second microreactor (a stainless steel round tube reactor with an inner diameter of 500 μm, and the reactor was heated in a constant temperature oil bath at 70° C.) for polymerization (ring-opening metathesis polymerization) with a residence time of 35 s (the length of the stainless steel round tube was adjusted so that the residence time of the reactants in the second microreactor was 35 s). After the reaction was completed, a block copolymer solution was obtained by flowing out from the outlet on the other side of the second microreactor.

[0111] (4) Dilution and cooling: The block copolymer solution is introduced into the fourth T-shaped mixer through a pipeline to be mixed with pure toluene solvent (flow rate is set to 15.2 mL / min), and the mixed solution flows into a stainless steel round tube with an inner diameter of 2.1 mm for further dilution and cooling. During this process, the concentration of the block copolymer solution is reduced from 127 mg / mL to 20 mg / mL, and the temperature of the solution is reduced from 70°C during the polymerization reaction to room temperature through the air cooling effect of the pipeline to obtain a cooled block copolymer dilute solution.

[0112] (5) Purification: The cooled block copolymer dilute solution is passed through a column containing Silicycle DMT metal scavenger (column capacity is 8 mL) to remove the residual catalyst online to ensure that the final product is environmentally friendly and non-toxic, thereby obtaining a purified block copolymer solution.

[0113] (6) Self-assembly (emulsion assembly): 100 mL of the purified block copolymer solution was collected into a 2 L beaker containing 1 L of PVA aqueous solution. Then, a high-speed homogenizer was used to stir the mixture at a speed of 6000 r / min for 30 s to form an oil-in-water (O / W) emulsion through shear force. The emulsion was then immediately placed in a constant temperature and humidity chamber at a temperature of 25°C and a humidity of 50%. After the solvent evaporated slowly, polymer porous microspheres were formed to obtain a blue block copolymer-based structural color material with a polymer molecular weight of 181 kDa and a maximum reflection wavelength of 461±5 nm.

[0114] Under these conditions, the output of block copolymer-based structural color materials can reach 0.52 kg / day.

[0115] Preparation of PVA aqueous solution: Polyvinyl alcohol (molecular weight 20000-30000 Da) was dissolved in Milli-Q water and heated to 95° C. to form a clear PVA aqueous solution with a concentration of 20 mg / mL.

[0116] (7) Structural color fine adjustment: With other conditions unchanged, by adjusting the flow rate ratio of the catalyst and the solvent (0.74 mL / min: 0.31 mL / min, 0.70 mL / min: 0.35 mL / min, 0.66 mL / min: 0.39 mL / min, 0.63 mL / min: 0.42 mL / min, 0.60 mL / min: 0.45 mL / min), polymer porous microspheres with different structural colors were obtained. The polymer molecular weights were 154 kDa, 169 kDa, 189 kDa, 198 kDa and 211 kDa, respectively, and the maximum reflection wavelengths were 411 nm, 428 nm, 452 nm, 477 nm and 486 nm, respectively. The actual pictures of polymer porous microspheres with different structural colors are shown in Fig. Figure 2(Macroscopic photographs and reflection optical micrographs of microspheres dispersed in water are shown), from left to right these are samples with maximum reflection wavelengths of 411 nm, 428 nm, 452 nm, 477 nm and 486 nm.

[0117] Figure 2 The polymer porous microspheres with different structural colors are clearly displayed, further demonstrating the effectiveness and accuracy of the method of the present invention.

[0118] Example 2

[0119] The same as Example 1, except that step (2) is specifically as follows: NB-PCL (norbornene-terminated polycaprolactone) macromonomer (molecular weight of 3000 Da, molecular weight distribution index of 1.10), NB-PEO (norbornene-terminated polyethylene glycol) macromonomer (molecular weight of 2000 Da, molecular weight distribution index of 1.09), and Grubbs third-generation catalyst (relative molecular weight of 884.53 Da) are prepared into 86 mmol / L, 86 mmol / L, and 2.5 mmol / L NB-PCL ultra-dry butyl acetate solution, NB-PEG ultra-dry butyl acetate solution, and Grubbs third-generation catalyst ultra-dry butyl acetate solution, respectively;

[0120] The NB-PCL ultra-dried butyl acetate solution, the NB-PEG ultra-dried butyl acetate solution, the Grubbs third-generation catalyst ultra-dried butyl acetate solution (catalyst solution) and the pure butyl acetate solvent were placed in reservoirs with continuous infusion pumps, respectively.

[0121] A blue block copolymer-based structural color material was obtained, the polymer molecular weight was 180 kDa, and the reflection wavelength was 459±4 nm.

[0122] Under these conditions, the output of block copolymer-based structural color materials can reach 0.52 kg / day.

[0123] Step (7) is specifically as follows: fine adjustment of structural color under other conditions: under other conditions, by adjusting the flow rate ratio of catalyst and solvent (0.74mL / min: 0.31mL / min, 0.70mL / min: 0.35mL / min, 0.66mL / min: 0.39mL / min, 0.63mL / min: 0.42mL / min, 0.60mL / min: 0.45mL / min), polymer porous microspheres with different structural colors are obtained, and the polymer molecular weights are 151kDa, 166kDa, 186kDa, 194kDa and 206kDa, respectively, and the maximum reflection wavelengths are 413nm, 430nm, 447nm, 472nm and 481nm, respectively. When only the solvent is changed and other conditions remain unchanged, the structural color of the obtained structural color material does not change significantly, indicating that the method has good repeatability.

[0124] Example 3

[0125] The same as Example 1, except that step (2) is specifically as follows: NB-PCL (norbornene-terminated polycaprolactone) macromonomer (molecular weight of 3000 Da, molecular weight distribution index of 1.10), NB-PEG (norbornene-terminated polyethylene glycol) macromonomer (molecular weight of 2000 Da, molecular weight distribution index of 1.09), and Grubbs third-generation catalyst (relative molecular weight of 884.53 Da) are prepared into 86 mmol / L, 86 mmol / L, and 2.5 mmol / L NB-PCL ultra-dry anisole solution, NB-PEG ultra-dry anisole solution, and Grubbs third-generation catalyst ultra-dry anisole solution, respectively;

[0126] The NB-PCL ultra-dried anisole solution, the NB-PEG ultra-dried anisole solution, the Grubbs third-generation catalyst ultra-dried anisole solution (catalyst solution) and the pure anisole solvent were placed in reservoirs with continuous infusion pumps, respectively.

[0127] Step (3) is specifically as follows: the catalyst solution (flow rate is set to 2.73 mL / min) and the pure anisole solvent (flow rate is set to 1.48 mL / min) are mixed uniformly in a first T-shaped mixer, and then mixed uniformly with the NB-PCL ultra-dry anisole solution (a solution of cycloolefin polymerization monomer 1, flow rate is set to 3.00 mL / min) through a second T-shaped mixer, and then introduced into a first microreactor (a stainless steel round tube reactor, the inner diameter of the tube is 1 mm, and the reactor is placed in a 70° C. constant temperature oil bath for heating) for polymerization reaction (ring-opening metathesis polymerization), the residence time is 35 s (the length of the stainless steel round tube is adjusted so that the residence time of the reactants in the first microreactor is 35 s), and after the reaction is completed, the first effluent is obtained by flowing out from the outlet on the other side of the first microreactor;

[0128] The first effluent and the NB-PEG ultra-dry anisole solution (a solution of cycloolefin polymerization monomer 2, with a flow rate set to 4.20 mL / min) were mixed evenly by a third T-shaped mixer, and passed into a second microreactor (a stainless steel round tube reactor with an inner diameter of 1 mm, and the reactor was heated in a 70° C. constant temperature oil bath) for polymerization (ring-opening metathesis polymerization) with a residence time of 45 s (the length of the stainless steel round tube was adjusted so that the residence time of the reactants in the second microreactor was 45 s). After the reaction was completed, a block copolymer solution was obtained by flowing out from the outlet on the other side of the second microreactor.

[0129] Step (4) is specially: the block copolymer solution is introduced into the fourth T-shaped mixer through a pipeline and mixed with a pure anisole solvent (flow velocity is set to 60.1 mL / min), and the mixed solution flows into a stainless steel round tube with an internal diameter of 2.1 mm to further dilute and cool. In this process, the concentration of the block copolymer solution is reduced from 127 mg / mL to 20 mg / mL, and the air cooling effect of the pipeline is simultaneously used to reduce the temperature of the solution from 70 ° C during the polymerization reaction to room temperature, thereby obtaining a cooled block copolymer dilute solution.

[0130] A blue block copolymer-based structural color material was obtained, with a polymer molecular weight of 169 kDa and a reflection wavelength of 420±7 nm.

[0131] Under these conditions, the output of block copolymer-based structural color materials can reach 2.08 kg / day.

[0132] Step (7) is specifically as follows: when other conditions remain unchanged, by adjusting the flow rate ratio of the catalyst and the solvent (2.64mL / min:1.55mL / min, 2.58mL / min:1.62mL / min, 2.52mL / min:1.68mL / min, 2.46mL / min:1.74mL / min, 2.40mL / min:1.80mL / min), polymer porous microspheres with different structural colors are obtained, and the polymer molecular weights are 185kDa, 189kDa, 194kDa, 199kDa and 205kDa, and the maximum reflection wavelengths are 445nm, 452nm, 464nm, 471nm and 480nm, respectively.

[0133] Example 4

[0134] The same as Example 1, except that step (2) is specifically as follows: NB-PCL (norbornene-terminated polycaprolactone) macromonomer (molecular weight of 3000 Da, molecular weight distribution index of 1.10), NB-PEG (norbornene-terminated polyethylene glycol) macromonomer (molecular weight of 2000 Da, molecular weight distribution index of 1.09), and Grubbs third-generation catalyst (relative molecular weight of 884.53 Da) are prepared into 86 mmol / L, 86 mmol / L, and 2.5 mmol / L NB-PCL ultra-dry anisole solution, NB-PEG ultra-dry anisole solution, and Grubbs third-generation catalyst ultra-dry anisole solution, respectively;

[0135] The NB-PCL ultra-dried anisole solution, the NB-PEG ultra-dried anisole solution, the Grubbs third-generation catalyst ultra-dried anisole solution (catalyst solution) and the pure anisole solvent were placed in reservoirs with continuous infusion pumps, respectively.

[0136] Step (3) is specifically as follows: the catalyst solution (flow rate is set to 8.10 mL / min) and the pure anisole solvent (flow rate is set to 8.71 mL / min) are mixed uniformly in a first T-shaped mixer, and then mixed uniformly with the NB-PCL ultra-dry anisole solution (a solution of cycloolefin polymerization monomer 1, flow rate is set to 12.00 mL / min) through a second T-shaped mixer, and then introduced into a first microreactor (a stainless steel round tube reactor, the inner diameter of the tube is 4 mm, and the reactor is placed in a 70° C. constant temperature oil bath for heating) for polymerization reaction (ring-opening metathesis polymerization), the residence time is 90 s (the length of the stainless steel round tube is adjusted so that the residence time of the reactants in the first microreactor is 90 s), and after the reaction is completed, the first effluent is obtained by flowing out from the outlet on the other side of the first microreactor;

[0137] The first effluent and the NB-PEG ultra-dry anisole solution (a solution of cycloolefin polymerization monomer 2, with a flow rate set to 28.80 mL / min) were mixed evenly by a third T-shaped mixer, and passed into a second microreactor (a stainless steel round tube reactor with an inner diameter of 4 mm, and the reactor was heated in a constant temperature oil bath at 70° C.) for polymerization (ring-opening metathesis polymerization) with a residence time of 90 s (the length of the stainless steel round tube was adjusted so that the residence time of the reactants in the second microreactor was 90 s). After the reaction was completed, a block copolymer solution was obtained by flowing out from the outlet on the other side of the second microreactor.

[0138] Step (4) is specially: the block copolymer solution is introduced into the fourth T-shaped mixer through a pipeline and mixed with a pure anisole solvent (flow velocity is set to 253.1 mL / min), and the mixed solution flows into a stainless steel round tube with an internal diameter of 5 mm to further dilute and cool. In this process, the concentration of the block copolymer solution is reduced from 131 mg / mL to 20 mg / mL, and the air cooling effect of the pipeline is simultaneously used to reduce the temperature of the solution from 70 ° C during the polymerization reaction to room temperature, thereby obtaining a cooled block copolymer dilute solution.

[0139] A blue block copolymer-based structural color material was obtained, with a polymer molecular weight of 175 kDa and a reflection wavelength of 431 ± 7 nm.

[0140] Under these conditions, the output of block copolymer-based structural color materials can reach 8.62 kg / day.

[0141] Step (7) is specifically as follows: when other conditions remain unchanged, by adjusting the flow rate ratio of the catalyst and the solvent (7.94mL / min:8.86mL / min, 7.79mL / min:9.01mL / min, 7.64mL / min:9.15mL / min, 7.51mL / min:9.29mL / min, 7.37mL / min:9.43mL / min), polymer porous microspheres with different structural colors are obtained, and the polymer molecular weights are 182kDa, 185kDa, 191kDa, 195kDa and 203kDa, and the maximum reflection wavelengths are 444nm, 451nm, 462nm, 470nm and 479nm, respectively.

[0142] Example 5

[0143] The same as Example 1, except that step (2) specifically comprises: preparing NB-PS (norbornene-terminated polystyrene) macromonomer (molecular weight of 8000 Da, molecular weight distribution index of 1.20), NB-PEG (norbornene-terminated polyvinylpyrrolidone) macromonomer (molecular weight of 500 Da, molecular weight distribution index of 1.07), and Grubbs third-generation catalyst (relative molecular weight of 884.53 Da) into 40 mmol / L, 300 mmol / L, and 2.5 mmol / L NB-PS ultra-dry anisole solution, NB-PEG ultra-dry anisole solution, and Grubbs third-generation catalyst ultra-dry anisole solution, respectively;

[0144] The NB-PS ultra-dried anisole solution, the NB-PEG ultra-dried anisole solution, the Grubbs third-generation catalyst ultra-dried anisole solution (catalyst solution) and the pure anisole solvent were placed in reservoirs with continuous infusion pumps, respectively.

[0145] Step (3) is specifically as follows: the catalyst solution (flow rate is set to 1.78 mL / min) and the pure anisole solvent (flow rate is set to 2.42 mL / min) are mixed uniformly in a first T-shaped mixer, and then mixed uniformly with the NB-PS ultra-dry anisole solution (a solution of cycloolefin polymerization monomer 1, flow rate is set to 3.00 mL / min) through a second T-shaped mixer, and then introduced into a first microreactor (a stainless steel round tube reactor, the inner diameter of the tube is 1 mm, and the reactor is placed in a 70° C. constant temperature oil bath for heating) for polymerization reaction (ring-opening metathesis polymerization), the residence time is 60 s (the length of the stainless steel round tube is adjusted so that the residence time of the reactants in the first microreactor is 60 s), and after the reaction is completed, the first effluent is obtained by flowing out from the outlet on the other side of the first microreactor;

[0146] The first effluent and the NB-PEG ultra-dry anisole solution (a solution of cycloolefin polymerization monomer 2, with a flow rate set to 6.00 mL / min) were mixed evenly by a third T-shaped mixer, and passed into a second microreactor (a stainless steel round tube reactor with an inner diameter of 1 mm, and the reactor was heated in a constant temperature oil bath at 70° C.) for polymerization (ring-opening metathesis polymerization) with a residence time of 90 s (the length of the stainless steel round tube was adjusted so that the residence time of the reactants in the second microreactor was 90 s). After the reaction was completed, a block copolymer solution was obtained by flowing out from the outlet on the other side of the second microreactor.

[0147] Step (4) is specially: the block copolymer solution is introduced into the fourth T-shaped mixer through a pipeline and mixed with a pure anisole solvent (flow velocity is set to 79.2 mL / min), and the mixed solution flows into a stainless steel round tube with an internal diameter of 2.1 mm to further dilute and cool. In this process, the concentration of the block copolymer solution is reduced from 140 mg / mL to 20 mg / mL, and the air cooling effect of the pipeline is simultaneously used to reduce the temperature of the solution from 70 ° C during the polymerization reaction to room temperature, thereby obtaining a cooled block copolymer dilute solution.

[0148] A red block copolymer-based structural color material was obtained, with a polymer molecular weight of 370 kDa and a reflection wavelength of 661 ± 6 nm.

[0149] Under these conditions, the output of block copolymer-based structural color materials can reach 2.68 kg / day.

[0150] Step (7) is specifically as follows: when other conditions remain unchanged, by adjusting the flow rate ratio of the catalyst and the solvent (1.71 mL / min: 2.49 mL / min, 1.65 mL / min: 2.54 mL / min, 1.60 mL / min: 2.60 mL / min, 1.55 mL / min: 2.65 mL / min, 1.50 mL / min: 2.70 mL / min), polymer porous microspheres with different structural colors are obtained, and the polymer molecular weights are 310 kDa, 325 kDa, 341 kDa, 356 kDa and 372 kDa, and the maximum reflection wavelengths are 621 nm, 632 nm, 640 nm, 647 nm and 658 nm, respectively.

[0151] Example 6

[0152] A method for finely adjusting the structural color of a block copolymer-based structural color material:

[0153] (1) Setting of reaction system: same as in Example 1.

[0154] (2) preparing solutions: NB-PS (norbornene-terminated polystyrene) macromonomer (molecular weight 4000 Da, molecular weight distribution index 1.16), NB-PEG (norbornene-terminated polyethylene glycol) macromonomer (molecular weight 4000 Da, molecular weight distribution index 1.13), and Grubbs third-generation catalyst (relative molecular weight 884.53 Da) were prepared into 40 mmol / L, 40 mmol / L, and 0.2 mmol / L NB-PS ultra-dry ethyl acetate solution, NB-PEG ultra-dry ethyl acetate solution, and Grubbs third-generation catalyst ultra-dry ethyl acetate solution, respectively;

[0155] The NB-PS ultra-dried ethyl acetate solution, the NB-PEG ultra-dried ethyl acetate solution, the Grubbs third-generation catalyst ultra-dried ethyl acetate solution (catalyst solution) and the pure ethyl acetate solvent were placed in reservoirs with continuous infusion pumps, respectively.

[0156] (3) Polymer synthesis: The catalyst solution (flow rate set to 2.36 mL / min) and pure ethyl acetate solvent (flow rate set to 1.84 mL / min) were mixed evenly in the first T-shaped mixer, and then mixed evenly with NB-PCL ultra-dry ethyl acetate solution (solution of cycloolefin polymerization monomer 1, flow rate set to 3.00 mL / min) through the second T-shaped mixer, and then introduced into the first microreactor (stainless steel round tube reactor, the inner diameter of the tube is 2 mm, the reactor is placed in a 70°C constant temperature oil bath for heating) for polymerization reaction (ring-opening metathesis polymerization), the residence time is 100 s (the length of the stainless steel round tube is adjusted so that the residence time of the reactants in the first microreactor is 100 s), and after the reaction is completed, the first effluent is obtained from the outlet on the other side of the first microreactor;

[0157] The first effluent and the NB-PEG ultra-dry ethyl acetate solution (a solution of cycloolefin polymerization monomer 2, with a flow rate set to 3.00 mL / min) were mixed evenly by a third T-shaped mixer, and introduced into a second microreactor (a stainless steel round tube reactor with an inner diameter of 2 mm, and the reactor was heated in a 70° C. constant temperature oil bath) for polymerization (ring-opening metathesis polymerization) with a residence time of 120 s (the length of the stainless steel round tube was adjusted so that the residence time of the reactants in the second microreactor was 120 s). After the reaction was completed, a block copolymer solution was obtained by flowing out from the outlet on the other side of the second microreactor.

[0158] (4) Dilution and cooling: The block copolymer solution is introduced into the fourth T-shaped mixer through a pipeline to be mixed with pure ethyl acetate solvent (flow rate is set to 37.7 mL / min), and the mixed solution flows into a stainless steel round tube with an inner diameter of 4 mm for further dilution and cooling. During this process, the concentration of the block copolymer solution is reduced from 94 mg / mL to 20 mg / mL, and at the same time, the temperature of the solution is reduced from 70°C during the polymerization reaction to room temperature through the air cooling effect of the pipeline, thereby obtaining a cooled block copolymer dilute solution.

[0159] (5) Purification: The cooled block copolymer dilute solution was passed through a column containing Silicycle DMT metal scavenger (column capacity was 20 mL) to remove the residual catalyst online to ensure that the final product was environmentally friendly and non-toxic, and a purified block copolymer solution was obtained with a polymer molecular weight of 2010 kDa.

[0160] (6) Self-assembly (bulk assembly): The purified block copolymer solution was scraped onto a polyethylene terephthalate (PET) film. After the solvent evaporated, a structural color film with a thickness of 5 μm and a wavelength of 521 ± 5 nm was obtained.

[0161] Under these conditions, the output of block copolymer-based structural color materials can reach 1.38 kg / day.

[0162] (7) Fine adjustment of structural color: With other conditions unchanged, by adjusting the flow rate ratio of catalyst and solvent (2.34mL / min:1.86mL / min, 2.32mL / min:1.88mL / min, 2.30mL / min:1.90mL / min, 2.28mL / min:1.92mL / min, 2.26mL / min:1.94mL / min), polymer structural color films with different structural colors were obtained. The molecular weights of the polymers were 2026kDa, 2042kDa, 2058kDa, 2074kDa and 2089kDa, and the maximum reflection wavelengths were 526nm, 532nm, 540nm, 547nm and 558nm, respectively.

[0163] Example 7

[0164] A method for finely adjusting the structural color of a block copolymer-based structural color material:

[0165] (1) Setting of reaction system: same as in Example 1.

[0166] (2) preparing solutions: preparing NB-PMMA (norbornene-terminated polymethyl methacrylate) macromonomer (molecular weight of 4000 Da, molecular weight distribution index of 1.16), NB-PS (norbornene-terminated polystyrene) macromonomer (molecular weight of 4000 Da, molecular weight distribution index of 1.13), and Grubbs third-generation catalyst (relative molecular weight of 884.53 Da) into 40 mmol / L, 40 mmol / L, and 0.2 mmol / L NB-PMMA ultra-dry ethyl acetate solution, NB-PS ultra-dry ethyl acetate solution, and Grubbs third-generation catalyst ultra-dry ethyl acetate solution, respectively;

[0167] The NB-PMMA ultra-dry ethyl acetate solution, the NB-PS ultra-dry ethyl acetate solution, the Grubbs third-generation catalyst ultra-dry ethyl acetate solution (catalyst solution) and the pure ethyl acetate solvent were placed in a reservoir with a continuous infusion pump, respectively.

[0168] (3) Polymer synthesis: The catalyst solution (flow rate set to 2.94 mL / min) and pure ethyl acetate solvent (flow rate set to 1.26 mL / min) were mixed evenly in the first T-shaped mixer, and then mixed evenly with NB-PCL ultra-dry ethyl acetate solution (solution of cycloolefin polymerization monomer 1, flow rate set to 3.00 mL / min) through the second T-shaped mixer, and then introduced into the first microreactor (stainless steel round tube reactor, the inner diameter of the tube is 2 mm, the reactor is placed in a 70°C constant temperature oil bath for heating) for polymerization reaction (ring-opening metathesis polymerization), the residence time is 120 s (the length of the stainless steel round tube is adjusted so that the residence time of the reactants in the first microreactor is 120 s), and after the reaction is completed, the first effluent is obtained from the outlet on the other side of the first microreactor;

[0169] The first effluent and the NB-PS ultra-dry ethyl acetate solution (a solution of cycloolefin polymerization monomer 2, with a flow rate set to 3.00 mL / min) were mixed evenly by a third T-shaped mixer, and introduced into a second microreactor (a stainless steel round tube reactor with an inner diameter of 2 mm, and the reactor was heated in a constant temperature oil bath at 70° C.) for polymerization (ring-opening metathesis polymerization) with a residence time of 120 s (the length of the stainless steel round tube was adjusted so that the residence time of the reactants in the second microreactor was 120 s). After the reaction was completed, a block copolymer solution was obtained by flowing out from the outlet on the other side of the second microreactor.

[0170] (4) Dilution and cooling: The block copolymer solution is introduced into the fourth T-shaped mixer through a pipeline to be mixed with pure ethyl acetate solvent (flow rate is set to 37.7 mL / min), and the mixed solution flows into a stainless steel round tube with an inner diameter of 4 mm for further dilution and cooling. During this process, the concentration of the block copolymer solution is reduced from 94 mg / mL to 20 mg / mL, and at the same time, the temperature of the solution is reduced from 70°C during the polymerization reaction to room temperature through the air cooling effect of the pipeline, thereby obtaining a cooled block copolymer dilute solution.

[0171] (5) Purification: The cooled block copolymer dilute solution was passed through a column containing Silicycle DMT metal scavenger (column capacity was 20 mL) to remove the residual catalyst online to ensure that the final product was environmentally friendly and non-toxic, and a purified block copolymer solution was obtained with a polymer molecular weight of 1632 kDa.

[0172] (6) Self-assembly (bulk assembly): The purified block copolymer solution was scraped onto a polyethylene terephthalate (PET) film. After the solvent evaporated, a structural color film with a thickness of 5 μm and a wavelength of 425±5 nm was obtained.

[0173] Under these conditions, the output of block copolymer-based structural color materials can reach 1.38 kg / day.

[0174] (7) Structural color fine-tuning: With other conditions unchanged, by adjusting the flow rate ratio of the catalyst and the solvent (2.91mL / min:1.29mL / min, 2.88mL / min:1.32mL / min, 2.85mL / min:1.35mL / min, 2.82mL / min:1.38mL / min, 2.79mL / min:1.41mL / min), polymer structural color films with different structural colors were obtained. The polymer molecular weights were 1648kDa, 1664kDa, 1680kDa, 1696kDa and 1712kDa, and the maximum reflection wavelengths were 432nm, 439nm, 446nm, 452nm and 461nm, respectively. The actual pictures of these five polymer structural color films with different structural colors are shown in Figure 3 , from left to right, the corresponding maximum reflection wavelengths are 432nm, 439nm, 446nm, 452nm and 461nm respectively. Figure 3 The polymer structural color films with different structural colors are clearly displayed, further demonstrating the effectiveness and accuracy of the method of the present invention.

[0175] Comparative Example 1

[0176] The same as Example 1, except that step (2) is specifically as follows: NB-PCL (norbornene-terminated polycaprolactone) macromonomer (molecular weight of 3000 Da, molecular weight distribution index of 1.10), NB-PEG (norbornene-terminated polyethylene glycol) macromonomer (molecular weight of 2000 Da, molecular weight distribution index of 1.09), and Grubbs third-generation catalyst (relative molecular weight of 884.53 Da) are prepared into 86 mmol / L, 86 mmol / L, and 2.5 mmol / L NB-PCL ultra-dry anisole solution, NB-PEG ultra-dry anisole solution, and Grubbs third-generation catalyst ultra-dry anisole solution, respectively;

[0177] The NB-PCL ultra-dried anisole solution, the NB-PEG ultra-dried anisole solution, the Grubbs third-generation catalyst ultra-dried anisole solution (catalyst solution) and the pure anisole solvent were placed in reservoirs with continuous infusion pumps, respectively.

[0178] Step (3) is specifically as follows: the catalyst solution (flow rate is set to 8.10 mL / min) and the pure anisole solvent (flow rate is set to 8.71 mL / min) are mixed uniformly in a first T-shaped mixer, and then mixed uniformly with the NB-PCL ultra-dry anisole solution (a solution of cycloolefin polymerization monomer 1, flow rate is set to 12.00 mL / min) through a second T-shaped mixer, and then introduced into a first microreactor (a stainless steel round tube reactor, the inner diameter of the tube is 4 mm, and the reactor is placed in a 70° C. constant temperature oil bath for heating) for polymerization reaction (ring-opening metathesis polymerization), the residence time is 10 s (the length of the stainless steel round tube is adjusted so that the residence time of the reactants in the first microreactor is 10 s), and after the reaction is completed, the first effluent is obtained by flowing out from the outlet on the other side of the first microreactor;

[0179] The first effluent and the NB-PEG ultra-dry anisole solution (a solution of cycloolefin polymerization monomer 2, with a flow rate set to 28.80 mL / min) were mixed evenly by a third T-shaped mixer, and passed into a second microreactor (a stainless steel round tube reactor with an inner diameter of 4 mm, and the reactor was heated in a constant temperature oil bath at 70° C.) for polymerization (ring-opening metathesis polymerization) with a residence time of 10 s (the length of the stainless steel round tube was adjusted so that the residence time of the reactants in the second microreactor was 10 s). After the reaction was completed, a block copolymer solution was obtained by flowing out from the outlet on the other side of the second microreactor.

[0180] Step (4) is specially: the block copolymer solution is introduced into the fourth T-shaped mixer through a pipeline and mixed with a pure anisole solvent (flow velocity is set to 253.1 mL / min), and the mixed solution flows into a stainless steel round tube with an internal diameter of 5 mm to further dilute and cool. In this process, the concentration of the block copolymer solution is reduced from 131 mg / mL to 20 mg / mL, and the air cooling effect of the pipeline is simultaneously used to reduce the temperature of the solution from 70 ° C during the polymerization reaction to room temperature, thereby obtaining a cooled block copolymer dilute solution.

[0181] After emulsion assembly, the product has no color. This is because the residence time of the reactants in the microreactor is too short, and the monomers are not completely converted, so that the first monomer is incorporated into the second block of the block copolymer, resulting in unclear chain structure and inability to phase separate to produce structural color materials with good phase separation structure.

[0182] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a block copolymer-based structural color material, characterized in that: The following steps are involved: The monomer 1 and the catalyst solution are mixed to carry out a first polymerization reaction, the product is mixed with the monomer 2 to carry out a second polymerization reaction to obtain a block copolymer, and the block copolymer is self-assembled to obtain the block copolymer-based structural color material.

2. The method for preparing a block copolymer-based structural color material according to claim 1, characterized in that: The preparation process of the block copolymer is carried out in a series of microreactors, which include the following devices connected in series in sequence: a first T-shaped mixer for mixing a catalyst and a solvent to prepare a catalyst solution, a second T-shaped mixer for mixing the catalyst solution and a monomer 1, a first microreactor for performing a first polymerization reaction, a third T-shaped mixer for mixing a product and a monomer 2, a second microreactor for performing a second polymerization reaction, a fourth T-shaped mixer for mixing the block copolymer and a solvent, a diluter for diluting the block copolymer, and an adsorption column for removing the catalyst.

3. The method for preparing a block copolymer-based structural color material according to claim 2, characterized in that: The monomer 1 and the monomer 2 are different cycloolefin polymerization monomers; and or, the molecular weight of the cycloolefin polymerization monomer is 500 to 10000 Da; and or, the topology of the block copolymer is bottle brush type; and / or, the temperature of the first polymerization reaction and the second polymerization reaction is 15 to 100° C.; And / or, the inner diameter of the pores of the microreactors connected in series is 0.5-5 mm.

4. The method for preparing a block copolymer-based structural color material according to claim 1, characterized in that: The self-assembly is emulsion assembly or bulk assembly.

5. The method for preparing a block copolymer-based structural color material according to claim 4, characterized in that: The emulsion assembly comprises: The block copolymer solution and the PVA aqueous solution are mixed and emulsified, and the block copolymer-based structural color material is obtained after the solvent evaporates.

6. The method for preparing a block copolymer-based structural color material according to claim 4, characterized in that: The body assembly comprises: The block copolymer solution is coated on the surface of the substrate, and the block copolymer-based structural color material is obtained after the solvent evaporates.

7. A block copolymer-based structural color material prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the block copolymer-based structural color material according to claim 7 in the preparation of pigments.

9. A method for finely adjusting the structural color of a block copolymer-based structural color material, characterized in that: The following steps are involved: The monomer 1 and the catalyst solution are mixed to carry out a first polymerization reaction, the product and the monomer 2 are mixed to carry out a second polymerization reaction to obtain a block copolymer, and the block copolymer is self-assembled to obtain a block copolymer-based structural color material.

10. The method according to claim 9, characterized in that The reflection wavelength of the block copolymer-based structural color material is 400-700 nm.

Citation Information

Patent Citations

  • Self-assembly substance based on brush-like block polymer and synthesis method and application thereof

    CN110016111A

  • Self-assembly of brush-shaped block polymer containing PEG segments as well as synthesis method and application of self-assembly

    CN112210071A

  • Application of amphiphilic block copolymer and preparation method of degradable photonic crystal microspheres

    CN113354824A

  • Method for synthesizing block copolymer brush by utilizing microfluidics

    CN113402699A

  • Rapid self-assembly of block copolymers to photonic crystals

    US20130324666A1